2015
DOI: 10.2217/nmt.14.53
|View full text |Cite
|
Sign up to set email alerts
|

Review of ‘the Potential Role of Arterial Stiffness in the Pathogenesis of Alzheimer’s Disease’

Abstract: SUMMARY Arterial stiffness is emerging as an important risk marker for poor brain aging and dementia through its associations with cerebral small vessel disease, stroke, β-amyloid deposition, brain atrophy and cognitive impairment. Arterial stiffness directly relates the detrimental effects of hypertension on peripheral organs with dire consequences for the extensive microvasculature structure of the kidneys and brain. In this review, we discuss the evidence linking arterial stiffness, hypertension and brain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 114 publications
(150 reference statements)
1
68
0
Order By: Relevance
“…Although it was previously known that extreme narrowing and/or stiffening of cerebral or peripheral arteries can lead to cerebrovascular problems (e.g., stroke, small vessel disease, vascular dementia), less was known about the impact of arterial elasticity on the volume of specific brain regions in relatively healthy individuals such as those included in this study (Hughes et al, 2015; Mattace-Raso et al, 2006; Power et al, 2011; Tanaka et al, 2000; van Sloten et al, 2015a; van Sloten et al, 2015b). These findings are consistent with the regionally specific association between cerebral blood flow (indexed using ASL) and anatomy found in older adults in one of our previous studies (Zimmerman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although it was previously known that extreme narrowing and/or stiffening of cerebral or peripheral arteries can lead to cerebrovascular problems (e.g., stroke, small vessel disease, vascular dementia), less was known about the impact of arterial elasticity on the volume of specific brain regions in relatively healthy individuals such as those included in this study (Hughes et al, 2015; Mattace-Raso et al, 2006; Power et al, 2011; Tanaka et al, 2000; van Sloten et al, 2015a; van Sloten et al, 2015b). These findings are consistent with the regionally specific association between cerebral blood flow (indexed using ASL) and anatomy found in older adults in one of our previous studies (Zimmerman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In one study, measurement of cardio-ankle vascular stiffness index using PWV 37 in 63 PD subjects showed no difference in cardio-ankle vascular stiffness index compared with normal controls 37 . Another study found that arterial stiffness was associated with cardiovascular autonomic dysfunction in patients with PD 36 . Greater arterial stiffness was associated with orthostatic hypotension, supine hypertension, nocturnal hypertension, and nondipping 38 .…”
Section: Arterial Stiffness and Cognitive Dysfunction In Parkinson's mentioning
confidence: 98%
“…The accumulated brain damage results in brain atrophy and cognitive dysfunction 30,31 . Other suggested etiologies include heart diastolic dysfunction 32 , medial temporal lobe atrophy 33 , reduced white matter integrity 34 , increased white matter hyperintensities 35 , progression of betaamyloid deposition 36 , and impaired renal function 26 .…”
mentioning
confidence: 99%
“…WMH are a well‐known risk factor for cognitive impairment . Cognitive impairment including dementia is also independently associated with arterial stiffness . An ABI greater than 1.30 and increased blood pressure variability are important predictors of cognitive impairment among patients without vascular diseases .…”
Section: Wmh and Arterial Stiffnessmentioning
confidence: 99%